2014
DOI: 10.1542/peds.2013-0652
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea in Preschool Children and Lactobacillus reuteri: A Randomized Controlled Trial

Abstract: OBJECTIVES: To evaluate whether daily administration of Lactobacillus reuteri DSM 17938 reduces the frequency and duration of diarrheal episodes and other health outcomes in day school children in Mexico. METHODS: Healthy children (born at term, aged 6–36 months) attending day care centers were enrolled in this randomized, double-blind, placebo-controlled trial. They received L reuteri DSM 17938 (dose 108 colony-forming unit;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 15 publications
3
59
0
8
Order By: Relevance
“…Recovery stools had a lesser relative abundance of Lactobacillus, thought to be a marker of a healthy microbiome. 26,27 While this finding was unexpected, a previous study of Indian children found that the abundance of Lactobacillus species increased at the end of diarrhea episodes and then decreased after 3 months of recovery. 28 Also, as compared with diarrhea stools, recovery stools had a greater relative abundance of genera of the order Clostridiales (Dorea, Blautia, Dialister, and Sporobacterium WAL_1855D).…”
Section: Discussionmentioning
confidence: 84%
“…Recovery stools had a lesser relative abundance of Lactobacillus, thought to be a marker of a healthy microbiome. 26,27 While this finding was unexpected, a previous study of Indian children found that the abundance of Lactobacillus species increased at the end of diarrhea episodes and then decreased after 3 months of recovery. 28 Also, as compared with diarrhea stools, recovery stools had a greater relative abundance of genera of the order Clostridiales (Dorea, Blautia, Dialister, and Sporobacterium WAL_1855D).…”
Section: Discussionmentioning
confidence: 84%
“…One RCT documented that a daily administration of L. reuteri for 3 months in 336 otherwise healthy, Mexican children attending day care centers a significant reduction in the number of episodes of diarrhoea, episodes of diarrhoea per child, mean duration of diarrhoea episodes and days with diarrhea per child both during the intervention and for the next 3-month follow-up period compared to the placebo group [56]. Another RCT carried out in malnourished Indonesian children found that the consumption of regular calcium milk with L. reuteri compared with regular calcium milk alone reduced the risk of diarrhoeal disease [57].…”
Section: Probiotics For Diarrhea In Children Attending Day Care Centersmentioning
confidence: 99%
“…Similarly, group counselling, where parents can hear the information and interact with the researchers and other parents can increase their understanding. For example, this approach was used recently in a placebo-controlled trial of probiotic use for infantile colic [27].…”
Section: Complete and Understandable Informationmentioning
confidence: 99%